Chapter 6. Morphology: Adjectives - Nesset, Tore (Septentrio Educational, 2015)
You may have asked yourself why Russian makes a distinction between short and long forms of adjectives. Why are the short forms only used in a limited number of constructions? Why do they only have nominative forms? Read this chapter and you will find answers to these and other questions regarding the history of adjectives. Section 6.1 explores the relationship between short and long forms, while sections 6.2 and 6.3 outline their declension. In section 6.4 you will find a discussion of the comparative and superlative degrees of adjectives. Section 6.5 sums up the main points. Download the video to learn more.